The effect of electron dose on positive polymethyl methacrylate resist for nanolithography of gold bowtie nanoantennas - Caroline Campbell; Abigail Casey; Gregory Triplett (Heliyon, 2022)
Plasmonic structures, such as bowtie nanoantennas, may be used in Surface Enhanced Raman Spectroscopy (SERS). Nanoantennas can be employed to amplify the biomolecular and chemical reactions, which is useful for biomedical applications. The electric field created by nanoantennas are optimized when the resonant wavelength of the probed laser light closely matches the resonant wavelength of the plasmonic structure. In this work, we fabricated several bowtie nanoantennas with varying geometric spacing for use with a 532 nm wavelength laser line in Raman Spectroscopy. The fabrication utilized nanolithography by electron beam lithography on a Raith Voyager, development, deposition, and metal lift-off. This study explored a specific bowtie nanoantenna geometry of 270 nm equilateral sides triangle pairs with 3 varying gap sizes, 50 nm, 20 nm, and 10 nm, and the effect of varying electron beam doses on the final structure of the nanoantenna. The results presented here, will show that the working dose factor range is 6.5–10.3 (650–10,300 μC/cm2) for 120 nm thick polymethyl methacrylate (PMMA), and with a 44.78% increase in dose, the footprint area increases between 5.9% and 10.7%.